Об одном методе расчета тепловых схем - Журбенко, Н.Г.; Лаптин, Ю.П. (Теорія оптимальних рішень, 2006)
A method of calculation of thermal schemes is proposed. The method is based on a construction of heat exchange unit model . The method consists in the iterated procedure. Basic operation on iteration is the solution of a linear equaions system. The results of solution of a set of equations are used for adjustment of parameters of model of heat exchange unit. The algorithm is used for software for optimum design of steam boilers.